Implementing skills-based grading in a linguistics course - O'Leary, M; Stockwell, R (Duke University Press, 2022)
This paper discusses how to implement ‘Skills-Based Grading’ (SBG) in linguistics, with a university-level course in formal semantics as a case study. Particular focus is given to transitioning to SBG from traditional grading. Regardless, of the grading system, all courses start out from a set of desired learning objectives, with final grades intended to reflect the extent to which these objectives have been achieved. Traditionally, grades are determined by a series of mandatory assessments and tests, for which somewhere between partial and full credit is awarded. In this paper, we illustrate how mastery of learning outcomes can be more directly measured by re-packaging them as “skills”. In SBG, students are given multiple opportunities to demonstrate full mastery of each skill. However, grading is all-or-nothing, with no partial credit awarded. SBG has been shown to improve student learning, encourage effective study, lower student stress, and achieve more equitable outcomes, and has been successfully adapted for linguistics courses in phonology (Zuraw et al. 2019) and semantics (O’Leary & Stockwell 2021). Here, we offer step-by-step instructions for creating an SBG course, covering skill types, skill groupings, opportunities, grading, and assessments.